Impact of role assignment on tertiary distance education students’ participation in online discussions and its consequence on grade performance - Abadi, Hajar Ghadirian Najaf (2015)
Online discussion forums have become widely adopted as a primary venue for discourse in distance courses. Participation in online discussions is essential element for successful learning experiences. Taking into account prior research suggesting lack of students’ participation in online discussions, this study conducted a quasiexperimental crossover research design with 48 registered students at an undergraduate blended course in UPM Education and Training (UPMET), hosted in Universiti Putra Malaysia (UPM) to investigate the effect of role assignment of peer moderator in advancing assigned students’ participation and that of their group members’ participation in online discussions. Moreover, the study examined the differences in levels of e-moderation supports enacted by peer moderators of high- and low-depth discussion forums. The influence of students’ participation on their final course grades was also analyzed. Eighty-four students were randomly assigned to groups of seven members that remained constant during the course. Students worked on seven weekly discussion topics during a regular semester. One week prior to onset of each online discussion, for each group, one student was randomly chosen as peer moderator who received two validated functional guidelines along with discussion topic for that particular week. Each student in the study received peer moderator role once. Log files of seven-week discussions were used to obtain the required data. Moreover, discussion transcripts of 30 peer moderators for two groups of high- and low-depth discussion forums- 15 each group- were collected and codified. Paired samples t-tests were used to compare students’ participation when assigned to the peer moderator role and when working as general responder. The results revealed that students in peer moderator role sent more messages (t(83) = 9.599, p < .001) with more characters (t(83) = 5.455, p < .001), replied more to messages of others (t(83) = 6.222, p < .001), logged to the system more with no posting (t(83) = 8.899, p < .001),and stayed longer in the system without posting (t(83) = 7.617, p < .001). Meanwhile,the multiple linear regression analyses indicated that five indicators of peer moderators’ participation together explained 66.1%, 60.5%, 15.0%, and 24.2% of the total variances for the group number of post, length of post, number of non-posting login, and length of non-posting login, respectively. Peer moderators’ non-posting participation significantly influenced all indicators of group participation. The results of independent samples t-tests indicated significant differences between high- and low-depth discussion forums in relation to the frequency of peer moderators’ e-moderation supports simulating: “access and motivation” (z = -4.672, p < .001), “socialization” (t(28) = 7.614, p < .001), “information exchange” (t(28) = 6.051, p < .001), “knowledge construction” (t(28) = 9.216, p < .001), and “development” (z = -3.150, p =.002). Using multiple linear regression analysis, one factor from quantity posting participation (number of post) and one factor from quantity non-posting participation (length of nonposting login) were identified as the predictors of students’ final course grades (R2 = .578, F(83) = 27.090, p < .001). In conclusion, these findings suggest that introduction of role assignment into courses utilizing online threaded discussions is an effective strategy that can result in increased participation, leading to better learning performance.